2021
DOI: 10.1177/08853282211064403
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered electrospinning and electrospraying approach: Effect of polymeric supplements on chondrocyte suspension

Abstract: Articular cartilage was expected to be one of the first tissues to be successfully engineered, but replicating the complex fibril architecture and the cellular distribution of the native cartilage has proven difficult. While electrospinning has been widely used to reproduce the depth-dependent fibre architecture in 3D scaffolds, the chondrocyte-controlled distribution remains an unsolved problem. To incorporate cells homogeneously through the depth of scaffolds, a combination of polymer electrospinning and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…10,45 Nonetheless, prior work has shown that combining the chondrocyte suspension with a polymeric hydrogel such as ALG was highly efficient in preventing cell death in this instance. 22 Indeed, a substantial percentage of chondrocytes was viable after 24 h of the fabrication process, particularly on the PG_D360. This metabolic behavior persisted and intensified during the course of 21 days in culture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,45 Nonetheless, prior work has shown that combining the chondrocyte suspension with a polymeric hydrogel such as ALG was highly efficient in preventing cell death in this instance. 22 Indeed, a substantial percentage of chondrocytes was viable after 24 h of the fabrication process, particularly on the PG_D360. This metabolic behavior persisted and intensified during the course of 21 days in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Three distinct scaffold architectures with controlled fiber alignment and porosity were fabricated with specific programmed fiber placements and characterized in terms of topography, water absorption capacity, and mechanical behavior. Similar to previous reports, 10,22,25,45 a cellular microintegration approach was also used in this work to seed cells directly onto the fibrous layers during scaffold's fabrication to obtain cell-laden constructs with a homogeneous cellular distribution. Chondrocytes were selected as the cell model, at this point, due to their low proliferative rate, and their subsequent difficulty in fully colonizing a 3D scaffold.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Multifunctional composite materials that consist of different components can be fabricated reliably at the nanometer scale [43][44][45][46]. Because of its many advantages, electrospinning has already been experimentally applied to bone [47,48], cartilage [49,50], tendon/ligament [51,52], skin [53,54], and cardiovascular [55,56] tissue engineering, as well as for wound dressings [57][58][59]. To date, however, no FDA-approved electrospun regenerative tissue engineering biomaterial is available commercially [42].…”
Section: Introductionmentioning
confidence: 99%